Evaluation of the physical health of adolescent in-patients in generic and secure services: retrospective case-note review. (June 2020) - Carney, Rebekah; Imran, Shermin; Law, Heather; Folstad, Siri; Parker, Sophie
Abstract : Aims and method: To assess physical health needs of adolescent in-patients by routine monitoring. A retrospective analysis of case notes was conducted on a 6-month intake to generic and secure adolescent mental health units in Greater Manchester, UK. Results: Fifty individuals were admitted (52% female, average age 15.84 years). Diagnoses varied and 66% were prescribed medications before admission. All had a physical health assessment, which identified various physical health risk factors. Average body mass index was 25.99 (range 15.8–44), and increased during in-patient treatment for 84% of individuals who had their body mass recorded more than once. A total of 28% of individuals smoked. Lipids and prolactin levels were elevated across the sample. Clinical implications: This evaluation strengthens the argument to optimise physical healthcare for adolescent in-patients and develop physical health interventions, particularly given that we observed elevated lipids and prolactin. Physical health and well-being may not be prioritised when assessing and managing young peoples' mental health, despite their increased vulnerability for comorbid conditions.